Resin composition for laser welding
The addition of metal borides or tungsten oxides to thermoplastic resin compositions enhances laser weldability, addressing shape-dependent welding intensity issues and ensuring strong, transparent welds in thermoplastic resin joints.
Patent Information
- Application Number
- JP2023196671
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-19
- Filing Date
- 2023-11-20
- Publication Date
- 2025-01-30
AI Technical Summary
Laser welding of thermoplastic resins is challenging due to variations in welding intensity based on the shape of the joint, leading to issues like incomplete melting, deformation, and poor weld strength, especially in joints without flanges or with narrow widths, and can result in resin decomposition and poor appearance.
Incorporating small amounts of metal borides or tungsten oxides into the transparent thermoplastic resin composition to enhance laser weldability, ensuring consistent welding intensity even in joints without flanges or narrow widths, while maintaining transparency and preventing resin melting.
The resin composition achieves high welding intensity with strong laser welds, maintaining excellent transparency and appearance, suitable for applications requiring high transparency such as medical and automotive components.
Smart Images

Figure 2025015383000001 
Figure 2025015383000002 
Figure 2025015383000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for laser welding, a laser light transmitting member, and a laser welded article. [Background technology]
[0002] Thermoplastic resins are molded into molded products by injection molding, etc., and these molded products are often joined together to form a product. Conventional joining methods include heat welding using a hot plate or infrared rays, welding using vibrations such as ultrasonic waves, joining with adhesives, and mechanical joining using screws or crimping, but there are problems with adhesives in terms of adhesive strength, and with mechanical joining in terms of cost, labor required for fastening, and increased weight.
[0003] In contrast, heat welding and vibration welding can join materials in a short time. Laser welding, a type of heat welding in particular, is a method in which laser light is irradiated onto layered resin molded products, allowing the laser light to pass through one of the irradiated transparent resin components and be absorbed by the other absorbent component, melting and fusing the materials together. Due to advantages such as high design freedom, excellent designability, and low running costs, this method is being rapidly adopted in a wide range of fields.
[0004] Laser welding of polycarbonate resin, which is a transparent thermoplastic resin, has also been proposed. Patent Document 1 describes the applicability of polycarbonate resin, in which polycarbonate resin is used for the lens and a polycarbonate-based material is used for the body, and the vehicle lighting components are integrated by laser welding. However, the aim of this is to prevent the occurrence of stress cracks in the body by obliquely irradiating the laser light, and there is no proposal to impart laser light absorbency to a laser light transmitting material made of polycarbonate resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-292741 A Summary of the Invention [Problem to be solved by the invention]
[0006] It is desirable to have a higher laser welding strength, but according to the inventor's study, it has been found that the laser welding strength is largely dependent on the shape. For example, when a flange or the like is provided at the joint as the part to be welded, the welding strength is likely to increase, but when there is no flange or the joint is narrow, when the laser light is irradiated from the laser light transmitting side member side, the laser light absorbing side member heats up and melts, but since no heat is stored near the welded part, the transmitting side member does not melt, the welding strength does not increase, and since the absorbing side member has a small heat capacity, it is prone to deformation. Therefore, there is a problem that the condition range for laser welding is narrow. In addition, when the laser light is strengthened to increase the welding strength, there is a problem that the resin decomposes, causing scorching and bubbles due to foaming, which deteriorates the appearance of the welded body. [Means for solving the problem]
[0007] As a result of extensive research to solve the above problems, the inventors discovered that by adding a small amount of metal boride or tungsten oxide to a transparent thermoplastic resin as a resin composition for the laser light transmitting side component, it is possible to prevent only the absorbing side component from melting, and to achieve high welding strength even in cases where there is no flange or the joint has a small heat capacity due to a narrow width, etc., and thus arrived at the present invention. The present invention relates to the following laser welding resin composition, laser light transmitting member, and laser welded article.
[0008] 1. A laser welding resin composition for a laser light transmitting member, comprising, per 100 parts by mass of a transparent thermoplastic resin (A), 0.000001 to 0.05 parts by mass of at least one metal boride (B1) selected from the group consisting of La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca, or 0.000001 to 0.05 parts by mass of at least one tungsten-based oxide (B2) selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide. 2. The resin composition for laser welding according to the above item 1, wherein the transparent thermoplastic resin (A) contains 10 to 100% by mass of a polycarbonate resin in the transparent thermoplastic resin (A). 3. The resin composition for laser welding according to the above item 1, further comprising 0.000001 to 0.05 parts by mass of carbon black per 100 parts by mass of the transparent thermoplastic resin (A). 4. The resin composition for laser welding according to the above item 1, further comprising a near-infrared absorbing dye in an amount of 0.000001 to 0.5 parts by mass per 100 parts by mass of the transparent thermoplastic resin (A). 5. The resin composition for laser welding according to the above item 1, further comprising 0.005 to 0.5 parts by mass of a phosphite-based antioxidant per 100 parts by mass of the transparent thermoplastic resin (A). 6. The laser weldable resin composition according to the above 1, wherein the polycarbonate resin contains 10 to 80 mass % of an aromatic polycarbonate resin having a terminal structure containing an ester group. 7. A laser beam transmitting member comprising the laser welding resin composition according to any one of 1 to 6 above. 8. The laser light transmitting member according to the above 7, which has a haze of 20% or less at a thickness of 1 mm. 9. A laser welded body in which the laser light transmitting member according to 7 above is laser welded to a laser light absorbing member. 10. The laser welded product according to the above 9, wherein the laser-light-absorbing side member contains 0.000001 to 0.05 parts by mass of carbon black per 100 parts by mass of the thermoplastic resin (B). 11. The laser welded product according to the above item 8, wherein the laser-absorbent side member contains 0.000001 to 0.5 parts by mass of a near-infrared absorbing dye per 100 parts by mass of the thermoplastic resin (B). 12. The laser-welded product according to the above item 9, wherein the laser-light-absorbing side member contains 0.005 to 0.5 parts by mass of a phosphite-based antioxidant per 100 parts by mass of the thermoplastic resin (B). 13. The laser welded body according to claim 9, wherein the haze at a thickness of 1 mm of the laser-absorbent side member is 20% or less. 14. The laser welded body according to claim 9, wherein the width of the laser welded portion between the laser-light-transmitting member and the laser-light-absorbing member is 0.5 to 10 mm. Effect of the Invention
[0009] The resin composition for laser welding of the present invention has excellent laser weldability that can achieve high welding strength even when there is no flange or when the heat capacity of the joint is small due to a narrow width of the joint, and provides a laser light transmission side member that can be firmly laser welded. In addition, since the condition range for laser welding is wide, strong laser welding can be easily achieved. In addition, the welded article exhibits excellent transparency, has excellent welding strength, and has a good appearance. Therefore, the laser welded article can be particularly suitably used for medical devices, wearable devices, and the like that require a high degree of transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present invention will be described in detail with reference to embodiments and examples, but the present invention should not be construed as being limited to the embodiments and examples shown below. In this specification, unless otherwise specified, the symbol "to" is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0011] The resin composition for laser welding of the present invention is characterized in that it contains, relative to 100 parts by mass of a transparent thermoplastic resin (A), 0.000001 to 0.05 parts by mass of at least one metal boride (B1) selected from the group consisting of La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca, or 0.000001 to 0.05 parts by mass of at least one tungsten-based oxide (B2) selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide, and is for use as a laser light transmitting member. The amount of the transparent thermoplastic resin (A) in the laser weldable resin composition of the present invention is preferably 50% by mass or more, more preferably 60% by mass or more, and is preferably less than 100% by mass.
[0012] [Transparent thermoplastic resin (A)] The transparent thermoplastic resin used in the laser welding resin composition of the present invention is not particularly limited, and examples thereof include thermoplastic resins such as polycarbonate resins; acrylic resins such as polymethyl methacrylate resins; amorphous polyester resins such as polyethylene terephthalate (PET) resins; polystyrene-based resins; cyclic polyolefin-based resins; and vinyl chloride resins, or polymer alloys consisting of two or more of these thermoplastic resins. Among these, from the viewpoint of transparency, it is preferable to use polycarbonate resin and acrylic resin, and polycarbonate resin is particularly preferable. As the transparent thermoplastic resin, a thermoplastic resin having a haze of 20% or less measured at a thickness of 1 mm is preferred, and specifically, a resin having a haze value of 20% or less measured using the transparent thermoplastic resin by the method described in the examples is preferred.
[0013] <Polycarbonate resin> There is no restriction on the specific type of polycarbonate resin, but examples thereof include polycarbonate polymers obtained by reacting a dihydroxy compound with a carbonate precursor. In this case, in addition to the dihydroxy compound and the carbonate precursor, a polyhydroxy compound or the like may be reacted. Also, a method of reacting carbon dioxide as a carbonate precursor with a cyclic ether may be used. Also, the polycarbonate polymer may be linear or branched. Furthermore, the polycarbonate polymer may be a homopolymer consisting of one type of repeating unit, or may be a copolymer having two or more types of repeating units. In this case, the copolymer may be selected from various copolymerization forms such as a random copolymer and a block copolymer. In addition, such a polycarbonate polymer is usually a thermoplastic resin.
[0014] Polycarbonate resins can be classified into aromatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aromatic carbons, and aliphatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aliphatic carbons, and either of these can be used. Among these, aromatic polycarbonate resins are preferred from the viewpoints of heat resistance, mechanical properties, electrical properties, etc. The amount of the polycarbonate resin in the transparent thermoplastic resin (A) is preferably from 10 to 100% by mass, and more preferably from 50 to 100% by mass.
[0015] Among the monomers that are raw materials for aromatic polycarbonate resins, examples of aromatic dihydroxy compounds include: Dihydroxybenzenes such as 1,2-dihydroxybenzene, 1,3-dihydroxybenzene (i.e., resorcinol), and 1,4-dihydroxybenzene; Dihydroxybiphenyls such as 2,5-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, and 4,4'-dihydroxybiphenyl; dihydroxynaphthalenes such as 2,2'-dihydroxy-1,1'-binaphthyl, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene; dihydroxydiaryl ethers such as 2,2'-dihydroxydiphenyl ether, 3,3'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 1,4-bis(3-hydroxyphenoxy)benzene, and 1,3-bis(4-hydroxyphenoxy)benzene;
[0016] 2,2-bis(4-hydroxyphenyl)propane (i.e. bisphenol A), 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e. bisphenol C), 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-methoxy-4-hydroxyphenyl)propane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-cyclohexyl-4-hydroxyphenyl)propane, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene, bis(4-hydroxyphenyl)methane, Bis(4-hydroxyphenyl)cyclohexylmethane, Bis(4-hydroxyphenyl)phenylmethane, Bis(4-hydroxyphenyl)(4-propenylphenyl)methane, Bis(4-hydroxyphenyl)diphenylmethane, Bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane (i.e. bisphenol AP), 1,1-bis(4-hydroxyphenyl)-1-naphthylethan, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)hexane, 1,1-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)octane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)nonane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)dodecane, Bis(hydroxyaryl)alkanes such as;
[0017] 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,4-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,5-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-propyl-5-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-phenylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-phenylcyclohexane, Bis(hydroxyaryl)cycloalkanes such as;
[0018] 9,9-bis(4-hydroxyphenyl)fluorene, Cardo structure-containing bisphenols such as 9,9-bis(4-hydroxy-3-methylphenyl)fluorene; 4,4'-dihydroxydiphenyl sulfide, Dihydroxydiaryl sulfides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide; 4,4'-dihydroxydiphenyl sulfoxide, Dihydroxydiaryl sulfoxides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide; 4,4'-dihydroxydiphenyl sulfone, dihydroxydiarylsulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenylsulfone; etc.
[0019] Of these, bis(hydroxyaryl)alkanes are preferred, and bis(4-hydroxyphenyl)alkanes are particularly preferred. In particular, from the standpoints of impact resistance, heat resistance, and transparency, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), and 1,1-bis(4-hydroxyphenyl)-1-phenylethane (i.e., bisphenol AP) are preferred. The aromatic dihydroxy compounds may be used alone or in any combination of two or more in any ratio.
[0020] Among the monomers that are raw materials for aromatic polycarbonate resins, examples of carbonate precursors include carbonyl halides, carbonate esters, etc. The carbonate precursors may be used alone or in any combination and ratio of two or more.
[0021] Specific examples of carbonyl halides include phosgene; haloformates such as bischloroformates of dihydroxy compounds and monochloroformates of dihydroxy compounds; and the like.
[0022] Specific examples of carbonate esters include diaryl carbonates such as diphenyl carbonate and ditolyl carbonate; dialkyl carbonates such as dimethyl carbonate and diethyl carbonate; biscarbonates of dihydroxy compounds, monocarbonates of dihydroxy compounds, and carbonates of dihydroxy compounds such as cyclic carbonates.
[0023] The method for producing the polycarbonate resin is not particularly limited, and any method can be used, such as interfacial polymerization, melt transesterification, pyridine method, ring-opening polymerization of a cyclic carbonate compound, and solid-phase transesterification of a prepolymer.
[0024] The molecular weight of the polycarbonate resin is arbitrary and may be appropriately selected and determined, but the viscosity average molecular weight [Mv] is usually 10,000 or more, preferably 14,000 or more, more preferably 16,000 or more, and usually 40,000 or less, preferably 30,000 or less. By setting the viscosity average molecular weight to the lower limit of the above range or more, the mechanical strength of the resin composition can be further improved, and it is more preferable when used in applications requiring high mechanical strength. On the other hand, by setting the viscosity average molecular weight to the upper limit of the above range or less, the decrease in the flowability of the resin composition can be suppressed and improved, and the molding processability can be improved to facilitate molding process. Two or more kinds of polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, polycarbonate resins having a viscosity average molecular weight outside the above-mentioned preferable range may be mixed.
[0025] The polycarbonate resin preferably contains a high molecular weight polycarbonate resin, for example, a polycarbonate resin having a viscosity average molecular weight [Mv] of 50000 to 95000. The viscosity average molecular weight of the high molecular weight polycarbonate resin is more preferably 55000 or more, even more preferably 60000 or more, of which 61000 or more, and particularly preferably 62000 or more, and more preferably 90000 or less, even more preferably 85000 or less, of which 80000 or less, particularly preferably 75000 or less, and particularly preferably 70000 or less.
[0026] When a high molecular weight polycarbonate resin is contained, it is preferably contained in the polycarbonate resin in an amount of 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The upper limit is preferably 40% by mass or less, more preferably 30% by mass or less.
[0027] In the present invention, the viscosity average molecular weight [Mv] of the polycarbonate resin is determined by measuring the intrinsic viscosity [η] (unit: dl / g) at a temperature of 25° C. using methylene chloride as a solvent and an Ubbelohde viscometer, and calculating the viscosity average molecular weight [Mv] from the Schnell viscosity formula, i.e., η = 1.23 × 10-4 Mv 0.83 This means the value calculated from The intrinsic viscosity [η] is the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.
[0028]
number
[0029] The polycarbonate resin preferably contains an aromatic polycarbonate resin having an end structure containing an ester group. The aromatic polycarbonate resin having an end structure containing an ester group has a low glass transition temperature and is easily melted. In addition, since the main skeleton of the aromatic polycarbonate resin is the same as that of ordinary polycarbonate, the compatibility with the laser light absorbing member is also good, so that the laser weldability is improved and high laser welding strength can be achieved. The terminal structure containing an ester group is not particularly limited as long as it contains an ester structure, but is preferably a group consisting of a combination of an ester group and a hydrocarbon group, or a combination of an ester group, a hydrocarbon group and -O-.
[0030] The terminal structure containing an ester group preferably has a terminal structure represented by the following formula (1): By using an aromatic polycarbonate resin having a terminal structure containing an ester group represented by formula (1), the glass transition temperature of the polycarbonate resin can be lowered.
[0031] [ka] In formula (1), R 1 R represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 30 carbon atoms. 2 each independently represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms. n represents an integer of 0 to 4. * represents a bonding site to another site.
[0032] R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 30 carbon atoms, preferably an alkyl group or alkenyl group having 10 or more carbon atoms, more preferably an alkyl group or alkenyl group having 12 or more carbon atoms, and even more preferably an alkyl group or alkenyl group having 14 or more carbon atoms. 1 is preferably an alkyl or alkenyl group having 22 or less carbon atoms, and more preferably an alkyl or alkenyl group having 18 or less carbon atoms. R 1 is preferably an alkyl group. The alkyl group and alkenyl group are preferably linear or branched alkyl or alkenyl groups, and more preferably linear alkyl or alkenyl groups. R 1 is preferably a hexadecyl ester or a 2-hexyldecyl ester, and particularly preferably a hexadecyl group. Also, R 1 may be located at any of the meta, para, or ortho positions, but is preferably located at the meta or para position, and more preferably at the para position.
[0033] R 2 each independently represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and is preferably a fluorine atom, a chlorine atom, a methyl group, an ethyl group, or a phenyl group, and more preferably a fluorine atom, a chlorine atom, or a methyl group. n represents an integer of 0 to 4, preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0034] The terminal structure represented by formula (1) can be added to an aromatic polycarbonate resin by using an end-capping agent such as parahydroxybenzoic acid hexadecyl ester.
[0035] Among the terminal structures represented by formula (1), it is particularly preferable to have either a parahydroxybenzoic acid hexadecyl ester structure or a parahydroxybenzoic acid 2-hexyldecyl ester structure, or both. The aromatic polycarbonate resin having the terminal structure represented by formula (1) may have one type of terminal structure represented by formula (1) or two or more types of terminal structures represented by formula (1).
[0036] The aromatic polycarbonate resin having a terminal structure containing an ester group may be used in combination with a terminal terminator having another structure. It is preferable that 80 mol% or more of the total terminal terminators used have the structure represented by the above formula (1), more preferably 90 mol% or more of the total terminal terminators used have the structure represented by the above formula (1), and particularly preferably that all the terminal terminators used have the structure represented by the above formula (1).
[0037] Other examples of the end terminator that may be used in combination include alkylphenols such as phenol, p-cresol, o-cresol, 2,4-xylenol, pt-butylphenol, o-allylphenol, p-allylphenol, p-hydroxystyrene, p-hydroxy-α-methylstyrene, p-propylphenol, p-cumylphenol, p-phenylphenol, o-phenylphenol, p-trifluoromethylphenol, p-nonylphenol, p-dodecylphenol, eugenol, amylphenol, hexylphenol, heptylphenol, octylphenol, nonylphenol, decylphenol, dodecylphenol, myristylphenol, palmitylphenol, stearylphenol, and behenylphenol, and alkyl esters of parahydroxybenzoic acid such as methyl ester, ethyl ester, propyl ester, butyl ester, amyl ester, hexyl ester, and heptyl ester. It is also possible to use two or more of the above monohydric phenols in combination.
[0038] The aromatic polycarbonate resin having a terminal structure containing an ester group is preferably a bisphenol type polycarbonate resin, more preferably a bisphenol A type polycarbonate resin. In addition, it is preferable that 50 mol % or more of the bisphenol type polycarbonate resin has at least one terminal structure represented by formula (1). When the aromatic polycarbonate resin has a terminal structure represented by formula (1), the terminal structure preferably consists solely of the terminal structure represented by formula (1).
[0039] The bisphenol A polycarbonate resin may also have other structural units than the carbonate structural units derived from bisphenol A and its derivatives. In the bisphenol polycarbonate resin, the carbonate structural units derived from bisphenol A and its derivatives preferably account for 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more of all structural units excluding terminal structures.
[0040] The viscosity average molecular weight (Mv) of the aromatic polycarbonate resin having a terminal structure containing an ester group is not particularly limited, but is preferably 14000 or more, more preferably 16000 or more, and particularly preferably 18000 or more, 19000 or more, and particularly preferably 20000 or more, and is preferably 36000 or less, and particularly preferably 34000 or less, 32000 or less, and particularly preferably 30000 or less. By setting the viscosity average molecular weight (Mv) to be equal to or more than the above lower limit and equal to or less than the above upper limit, the member has high strength, has good meltability with laser light, and tends to have improved laser weldability. In addition, aromatic polycarbonate resins having a terminal structure containing two or more types of ester groups with different viscosity average molecular weights may be mixed and used. In this case, aromatic polycarbonate resins having a terminal structure containing an ester group with a viscosity average molecular weight outside the above range may be mixed to adjust the viscosity average molecular weight within the above range. The amount of the aromatic polycarbonate resin having a terminal structure containing an ester group in the polycarbonate resin is preferably from 0 to 90% by mass, more preferably from 10 to 80% by mass, and further preferably from 15 to 75% by mass.
[0041] The polycarbonate resin may be not only virgin resin, but also polycarbonate resin regenerated from used products (so-called material recycled polycarbonate resin), or polycarbonate resin produced from polycarbonate resin chemically decomposed back to its raw materials (so-called chemically recycled polycarbonate resin), and it is also preferable to contain both virgin resin and recycled resin, or to consist of recycled polycarbonate resin. When recycled polycarbonate resin is contained, the proportion of recycled polycarbonate resin in the polycarbonate resin is preferably 40% or more, 50% or more, 60% or more, or 80% or more, and it is also preferable that the recycled polycarbonate resin is 100%. Preferred examples of used products include various sheet materials, optical recording media such as optical disks (CDs, DVDs), light guide plates, transparent vehicle components such as automobile window glass, automobile headlamp lenses, and windshields, containers such as water bottles, eyeglass lenses, various cover materials, soundproof walls, glass windows, corrugated sheets, and other building components. In addition, as recycled polycarbonate resins, crushed products obtained from non-conforming products, sprues, or runners during molding, or pellets obtained by melting these can also be used.
[0042] <Acrylic resin> The acrylic resin is preferably a methyl (meth)acrylate-based resin, and the monomer amount of the structural unit of methyl (meth)acrylate is preferably 80 mol% or more, preferably 90 mol% or more, based on the total monomer amount of all structural units. The acrylic resin is also preferably a copolymer of methyl (meth)acrylate and other methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, or the like. Examples of such copolymers include copolymers of methyl (meth)acrylate and a (meth)acrylate compound having an aromatic compound in the side chain, specifically phenyl methacrylate-methyl methacrylate-methyl acrylate copolymer and 4-phenylbenzyl methacrylate-methyl methacrylate-methyl acrylate copolymer. In this specification, unless otherwise specified, "(meth)acrylate" refers to both or either of acrylate and methacrylate.
[0043] The acrylic resin preferably has a mass average molecular weight of 5,000 or more, more preferably 8,000 or more, further preferably 10,000 to 200,000, and particularly preferably 50,000 to 150,000. The mass average molecular weight of the acrylic resin is a value measured by gel permeation chromatography using standard polystyrene as a standard sample.
[0044] The methods for producing acrylic resins are generally roughly divided into emulsion polymerization, suspension polymerization, and continuous polymerization, and the acrylic resin used in the present invention is preferably an acrylic resin produced by a continuous polymerization method. The continuous production method can be further divided into a continuous bulk polymerization method and a continuous solution polymerization method, and the acrylic resin produced by either method can be used in the present invention. The acrylic resin may be used alone or in combination of two or more kinds.
[0045] As described above, the transparent thermoplastic resin (A) is preferably a polycarbonate resin or an acrylic resin, but when a thermoplastic resin other than the polycarbonate resin or the acrylic resin is contained, the content thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, per 100 parts by mass of the polycarbonate resin or the acrylic resin.
[0046] [Metal borides (B1), tungsten oxides (B2)] The resin composition for laser welding of the present invention contains at least one metal boride (B1) selected from the group consisting of La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca, or at least one tungsten-based oxide (B2) selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide.
[0047] Metal boride (B1) is a compound that has the ability to absorb light in the wavelength range of laser light, and has a large number of free electrons to generate plasma resonance vibration. When laser light is incident on metal boride (B1), the free electrons are excited according to the frequency of the light, causing collective vibration of the electrons, and energy is absorbed and radiated. The absorption wavelength at this time depends on the energy structure of the free electron density, and has a plasma absorption wavelength in the vicinity of the wavelength range of 800 to 1200 nm of Nd:YAG laser and semiconductor laser light.
[0048] The metal borides (B1) are represented by the general formula XB 6 (wherein X is one or more metal elements selected from La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca), and XB 4 , X.B. 12 The boron compound may contain small amounts of other borides represented by the formula (I) and the like.
[0049] Among the above, La and Ce are preferable as X. LaB 6 , CeB 6 is preferred, particularly LaB 6 is preferred.
[0050] The metal boride (B1) is preferably in the form of fine particles, and the average dispersed particle size is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 85 nm or less. The lower limit is not particularly limited, but for example, 1 nm or more is preferable because it is easy to produce industrially. The average dispersed particle size can be measured by a particle size measuring device based on the dynamic light scattering method, and the median value (D 50 ).
[0051] The tungsten oxide (B2) is selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide, and is tungsten oxide WO 3 By adding potassium, rubidium, cesium, and thallium elements M to tungsten oxide, a composite tungsten oxide called WO 3 Free electrons are generated within the compound, and strong absorption characteristics due to the free electrons are apparent, particularly in the near-infrared region, making the compound effective as a laser light absorbing compound with a wavelength of around 1000 nm. When the composite tungsten oxide is expressed as MxWyOz (wherein M is potassium, rubidium, cesium or thallium, W is tungsten, and O is oxygen), a composite tungsten oxide that satisfies the relationships 0.01≦x / y≦1 and 2.0≦z / y≦3 is more preferable.
[0052] The tungsten oxide (B2) is preferably in the form of fine particles, and the average dispersed particle size is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 85 nm or less. The lower limit is not particularly limited, but for example, 1 nm or more is preferable because it is easy to produce industrially. The average dispersed particle size can be measured by a particle size measuring device based on the dynamic light scattering method, and the median value (D 50 ).
[0053] The content of the metal boride (B1) or tungsten oxide (B2) is 0.000001 to 0.05 parts by mass relative to 100 parts by mass of the transparent thermoplastic resin (A). By setting the content at such a level, transparency and laser weldability are improved. The content is preferably 0.00001 parts by mass or more, particularly 0.0001 parts by mass or more, 0.0005 parts by mass or more, 0.001 parts by mass or more, 0.0015 parts by mass or more, particularly 0.002 parts by mass or more, and preferably 0.04 parts by mass or less, particularly 0.03 parts by mass or less, 0.02 parts by mass or less, 0.01 parts by mass or less, particularly 0.005 parts by mass or less. The preferred total amount when (B1) and (B2) are both contained is also this amount.
[0054] [Carbon black] The resin composition for laser welding of the present invention preferably contains carbon black. Carbon black is usually blended as a laser absorbent in the laser-absorbent side member, but it is also preferably blended in the resin composition for the laser-transmitting side member of the present invention. When carbon black is contained, the content is preferably 0.000001 to 0.05 parts by mass, more preferably 0.00001 parts by mass or more, of which 0.0001 parts by mass or more, 0.001 parts by mass or more, and particularly preferably 0.003 parts by mass or more, relative to 100 parts by mass of the transparent thermoplastic resin (A), and is more preferably 0.04 parts by mass or less, of which 0.03 parts by mass or less, 0.02 parts by mass or less, 0.01 parts by mass or less, and particularly preferably 0.005 parts by mass or less. When carbon black is contained in the resin composition for the laser-light-absorbing side member described below, the content of carbon black per 100 parts by mass of the thermoplastic resin (B) is the same as above.
[0055] The carbon black is not limited in its manufacturing method and raw material type, and any conventionally known carbon black can be used, such as furnace black, channel black, acetylene black, and ketjen black. Among these, furnace black is preferred from the standpoint of coloring properties and cost. The primary particle size of the carbon black can be appropriately selected, and is preferably 12 to 60 nm, more preferably 12 to 40 nm, and even more preferably 12 to 22 nm.
[0056] [Near infrared light absorbing dye] It is also preferable that the resin composition for laser welding of the present invention further contains a near-infrared absorbing dye other than the metal boride (B1) and the tungsten oxide (B2). The near-infrared absorbing dye is a laser light absorbent that selectively absorbs light of a specific wavelength region in the near-infrared light region (750 to 2500 nm, preferably 1000 to 1100 nm), and is usually often blended in the laser light absorbing side member, but it is also preferable to contain it in the resin composition for the laser light transmitting side member of the present invention.
[0057] Other near-infrared light absorbing dyes that can be used include known dyes, such as cyanine dyes having a polymethine skeleton or the like, phthalocyanine dyes having aluminum, zinc, vanadium, or the like as a central metal, various naphthalocyanine dyes, nickel dithiolene complexes, squarium dyes, quinone compounds, diimmonium compounds, azo compound cyanine complexes, phenylenediamine complexes, dithiol metal complexes, and naphthoquinone dyes.
[0058] When a near-infrared light absorbing dye is contained, the content is preferably 0.000001 to 0.5 parts by mass, more preferably 0.00001 parts by mass or more, of which 0.0001 parts by mass or more, 0.001 parts by mass or more, 0.002 parts by mass or more, and particularly 0.003 parts by mass or more, and more preferably 0.3 parts by mass or less, of which 0.2 parts by mass or less, 0.1 parts by mass or less, 0.05 parts by mass or less, 0.04 parts by mass or less, 0.03 parts by mass or less, 0.02 parts by mass or less, 0.01 parts by mass or less, and particularly 0.005 parts by mass or less, is preferred.
[0059] [Phosphite-based antioxidants] It is also preferable that the laser weldable resin composition of the present invention further contains a phosphite-based antioxidant. The phosphite compound has the general formula: P(OR) 3 where R represents a monovalent or divalent organic group.
[0060] Examples of such phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyldiphenyl phosphite, dioctyl monophenyl phosphite, monodecyldiphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, distearyl pentaerythritol diphosphite, bis(2,4- di-tert-butyl-4-methylphenyl)pentaerythritol phosphite, bis(2,6-di-tert-butylphenyl)octyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene-diphosphite, 6-[3-(3-tert-butyl-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]-dioxaphosphepine, and the like.
[0061] Among such phosphite compounds, aromatic phosphite compounds represented by the following formula (3) or the following formula (2) having a spiro ring skeleton are more preferred.
[0062] [ka] [In formula (2), R 1 , R 2 and R 3 may be the same or different and represent an aryl group having 6 to 30 carbon atoms.
[0063] [ka] [In formula (3), R 4 and R 5 may be the same or different and represent an aryl group having 6 to 30 carbon atoms.
[0064] As the phosphite-based antioxidant represented by the above formula (2), triphenyl phosphite, tris(mononylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, etc. are preferred, and tris(2,4-di-tert-butylphenyl) phosphite is more preferred. Specific examples of such phosphite-based antioxidants include "Adeka STAB 1178" manufactured by ADEKA Corporation, "Sumilizer TNP" manufactured by Sumitomo Chemical Co., Ltd., "JP-351" manufactured by Johoku Chemical Industry Co., Ltd., "Adeka STAB 2112" manufactured by ADEKA Corporation, "Irgafos 168" manufactured by BASF, and "JP-650" manufactured by Johoku Chemical Industry Co., Ltd.
[0065] As the phosphite-based antioxidant represented by the above formula (3), those having a pentaerythritol diphosphite structure such as bis(2,4-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are particularly preferred. Specific examples of such phosphite-based antioxidants include "ADEKA STAB PEP-36" manufactured by ADEKA, "Doverphos S-9228" manufactured by Doverchemical, and "SONGNOX 6260" manufactured by SONGWON.
[0066] The phosphite antioxidant may be contained alone or in any combination and ratio of two or more kinds.
[0067] The content of the phosphite antioxidant is preferably 0.005 to 0.5 parts by mass, preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and also preferably 0.4 parts by mass or less, further preferably 0.3 parts by mass or less, among which 0.2 parts by mass or less, 0.1 parts by mass or less, and particularly preferably 0.05 parts by mass or less, based on 100 parts by mass of the transparent thermoplastic resin (A). By including it in such an amount, it is possible to further improve excellent color tone (haze), heat discoloration resistance, and wet heat discoloration resistance.
[0068] [Alkyl acid phosphates, their metal salts, organic phosphonic acids] The laser weldable resin composition of the present invention also preferably contains an alkyl acid phosphate or a metal salt thereof, or an organic phosphonic acid.
[0069] The alkyl acid phosphate is preferably one represented by the following formula (4). O=P(OH) n (OR) 3-n …(4) [In formula (4), R is an alkyl group having 9 to 30 carbon atoms, and n is an integer of 1 or 2. When n is 1, the two Rs may be the same or different.] The alkyl acid phosphate is preferably represented by the above formula (4), and the alkyl acid phosphate metal salt is preferably a metal salt such as a zinc salt or an aluminum salt of the alkyl acid phosphate represented by the above formula (4).
[0070] The alkyl group represented by R in the above formula (4) may be a linear alkyl group or may have a branch. Specific examples of the alkyl group represented by R include nonyl, isononyl, decyl, isodecyl, dodecyl, tridecyl, isotridecyl, tetradecyl, hexadecyl, oct ... Examples include octadecyl (ie, stearyl), eicosyl, and tetracosyl groups. The number of carbon atoms in the alkyl group is more preferably 13, 18, or 24, and the alkyl acid phosphate is particularly preferably a mixture of distearyl acid phosphate (n=1) and monostearyl acid phosphate (n=2).
[0071] As the metal salt of alkyl acid phosphate, a mixture of distearyl acid phosphate zinc salt (n=1) and monostearyl acid phosphate zinc salt (n=1) is particularly preferred.
[0072] The organic phosphonic acid is preferably one represented by the following formula (5). RP(=O)(OH) 2 …(5) [In formula (5), R is a group selected from the group consisting of an aryl group, an aralkyl group, and an alkyl group.] In the above formula (5), the aryl group includes, for example, phenol, hydroxyphenyl, naphthyl, etc., the aralkyl group includes, for example, benzyl, p-hydroxybenzyl, 4-hydroxy-2,5-di-t-butylbenzyl, etc., and the alkyl group includes, for example, ethyl, propyl, butyl, hexyl, octyl, etc.
[0073] Specific preferred examples of the organic phosphonic acid include phenylphosphonic acid, tolylphosphonic acid, benzylphosphonic acid, p-hydroxybenzylphosphonic acid, 4-hydroxy-3,5-di-t-butylbenzylphosphonic acid, ethylphosphonic acid, etc. Among these, arylphosphonic acids such as phenylphosphonic acid are preferred.
[0074] The content of alkyl acid phosphate, its metal salt, and organic phosphonic acid is preferably 0.0000005 to 0.1 parts by mass relative to 100 parts by mass of the transparent thermoplastic resin (A). By containing them in such an amount, a laser welding member having high transparency and excellent heat (humid heat) discoloration resistance and capable of strong laser welding can be provided, and the laser welded welded body can be made to have excellent transparency and excellent heat discoloration resistance and moist heat discoloration resistance. The content is more preferably 0.00001 parts by mass or more, particularly preferably 0.0001 parts by mass or more, 0.0005 parts by mass or more, and particularly preferably 0.001 parts by mass or more, and more preferably 0.05 parts by mass or less, and particularly preferably 0.01 parts by mass or less.
[0075] [Release agent] The laser welding resin composition of the present invention preferably contains a release agent (lubricant). Examples of the release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.
[0076] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0077] The aliphatic carboxylic acid in the ester of aliphatic carboxylic acid and alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term aliphatic is used to include alicyclic compounds.
[0078] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.
[0079] The above ester may contain an aliphatic carboxylic acid and / or alcohol as an impurity. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be used alone or in any combination and ratio of two or more.
[0080] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.
[0081] Examples of aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons also include alicyclic hydrocarbons. These hydrocarbons may be partially oxidized. Among these, paraffin wax, polyethylene wax, or a partial oxide of polyethylene wax is preferred, and paraffin wax and polyethylene wax are more preferred. The number average molecular weight of the aliphatic hydrocarbon is preferably 5,000 or less. The aliphatic hydrocarbon may be a single substance, but a mixture of substances having various constituent components and molecular weights can also be used as long as the main component is within the above range.
[0082] Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone.
[0083] The above-mentioned release agents may be contained alone or in any combination and ratio of two or more kinds.
[0084] The content of the release agent is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, based on 100 parts by mass of the transparent thermoplastic resin (A). If the content of the release agent is less than the lower limit of the above range, the effect of releasability may be insufficient, whereas if the content of the release agent is more than the upper limit of the above range, there is a possibility that the hydrolysis resistance may decrease and the mold may be contaminated during injection molding.
[0085] [Ultraviolet absorber] It is also preferable that the laser weldable resin composition of the present invention further contains an ultraviolet absorber. Examples of the ultraviolet absorbing agent include inorganic ultraviolet absorbing agents such as cerium oxide and zinc oxide; and organic ultraviolet absorbing agents such as benzotriazole compounds, benzophenone compounds, salicylate compounds, cyanoacrylate compounds, triazine compounds, oxanilide compounds, malonic acid ester compounds, hindered amine compounds, and oxalic acid anilide compounds. Among these, organic ultraviolet absorbing agents are preferred, and benzotriazole compounds are more preferred. By selecting an organic ultraviolet absorbing agent, the transparency and mechanical properties of the resin composition of the present invention can be improved.
[0086] Specific examples of the benzotriazole compound include, for example, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole. t-amyl)-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] and the like. Among these, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] are preferred, and 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole is particularly preferred. Specific examples of such benzotriazole compounds include "Seesorb 701", "Seesorb 705", "Seesorb 703", "Seesorb 702", "Seesorb 704", and "Seesorb 709" manufactured by Shipro Chemical Co., Ltd., "Biosorb 520", "Biosorb 582", "Biosorb 580", and "Biosorb 583" manufactured by Kyodo Pharmaceutical Co., Ltd., "Chemisorb 71" and "Chemisorb 72" manufactured by Chemipro Chemical Co., Ltd., "Cyasorb UV5411" manufactured by Cytec Industries, "LA-32", "LA-38", "LA-36", "LA-34", and "LA-31" manufactured by ADEKA, and "Tinuvin P", "Tinuvin 234", "Tinuvin 326", "Tinuvin 327", and "Tinuvin 328" manufactured by BASF.
[0087] Specific examples of the benzophenone compound include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-n-dodecyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone. Specific examples of such benzophenone compounds include Seesorb 100, Seesorb 101, and Seesorb 201 manufactured by Shipro Chemical Co., Ltd. Examples of such compounds include "Seesorb 101S", "Seesorb 102", and "Seesorb 103" manufactured by Kyodo Pharmaceutical Co., Ltd., "Biosorb 100", "Biosorb 110", and "Biosorb 130" manufactured by Chemipro Kasei Co., Ltd., "Chemisorb 10", "Chemisorb 11", "Chemisorb 11S", "Chemisorb 12", "Chemisorb 13", and "Chemisorb 111" manufactured by BASF, "Ubinur 400" manufactured by BASF, "Ubinur M-40" manufactured by BASF, "Ubinur MS-40" manufactured by BASF, "Cyasorb UV9", "Cyasorb UV284", "Cyasorb UV531", and "Cyasorb UV24" manufactured by Cytec Industries, and "ADK STAB 1413" and "ADK STAB LA-51" manufactured by ADEKA.
[0088] Specific examples of salicylate compounds include phenyl salicylate, 4-tert-butylphenyl salicylate, etc., and specific examples of such salicylate compounds include "Seesorb 201" and "Seesorb 202" manufactured by Shipro Chemical Co., Ltd., and "Chemisorb 21" and "Chemisorb 22" manufactured by Chemipro Chemical Co., Ltd.
[0089] Specific examples of cyanoacrylate compounds include ethyl-2-cyano-3,3-diphenylacrylate, 2-ethylhexyl-2-cyano-3,3-diphenylacrylate, and the like. Specific examples of such cyanoacrylate compounds include "Seesorb 501" manufactured by Shipro Chemical Co., Ltd., "Biosorb 910" manufactured by Kyodo Pharmaceutical Co., Ltd., "Ubisolator 300" manufactured by Daiichi Chemical Co., Ltd., "Ubinur N-35" and "Ubinur N-539" manufactured by BASF, and the like.
[0090] A specific example of the oxalinide compound is 2-ethoxy-2'-ethyl oxalinic acid bis-arylidine. A specific example of such an oxalinide compound is "Sandubor VSU" manufactured by Clariant.
[0091] As the malonic acid ester compound, 2-(alkylidene)malonic acid esters are preferable, and 2-(1-arylalkylidene)malonic acid esters are more preferable. Specific examples of such malonic acid ester compounds include "PR-25" manufactured by Clariant Japan and "B-CAP" manufactured by BASF.
[0092] When the laser welding resin composition of the present invention contains an ultraviolet absorbing agent, the content thereof is usually 0.05 parts by mass or more, preferably 0.1 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the transparent thermoplastic resin (A). If the content of the ultraviolet absorbing agent is less than the lower limit of the above range, the effect of improving weather resistance may be insufficient, and if the content of the ultraviolet absorbing agent is more than the upper limit of the above range, mold deposits and the like may occur, causing mold contamination. The ultraviolet absorbing agent may be contained alone or in any combination and ratio of two or more kinds.
[0093] [Other ingredients] The resin composition for laser welding of the present invention may contain other components in addition to those described above, as necessary, as long as the desired physical properties are not significantly impaired. Examples of other components include various resin additives, other resins, etc. Note that the other components may be contained alone or in any combination and ratio of two or more.
[0094] <Resin additives> Examples of resin additives include flame retardants, flame retardant auxiliaries, fillers, fluorescent whitening agents, impact resistance improvers, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, compatibilizers, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more. Examples of the filler include fibrous or granular fillers such as glass fibers. When the refractive index difference between the glass fiber and the resin composition is preferably less than 0.01, more preferably less than 0.005 at a wavelength of 550 nm, the transparency of the laser light transmitting member is excellent. In addition to the above-mentioned components, other resins, additives, etc. may be contained as necessary, so long as the desired physical properties are not significantly impaired.
[0095] <Other resins> Other resins include, for example, thermoplastic polyester resins such as polyethylene terephthalate resin, polytrimethylene terephthalate resin, and polybutylene terephthalate resin; styrene-based resins such as polystyrene resin, high impact polystyrene resin (HIPS), acrylonitrile-styrene copolymer (AS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), and acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resins; polyimide resins; polyetherimide resins; polyurethane resins; polyphenylene ether resins; polyphenylene sulfide resins; and polysulfone resins. The other resins may be contained either alone or in any combination and ratio of two or more kinds. However, when other resins are contained, the content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, per 100 parts by mass of the transparent thermoplastic resin (A).
[0096] [Production of resin composition] There is no limitation on the method for producing the laser weldable resin composition of the present invention, and a wide variety of known methods for producing resin compositions can be used. Specific examples include a method in which the above-mentioned essential components and other components to be added as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded with a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, etc. In this case, it is also preferable to side-feed each component as necessary.
[0097] In addition, for example, the laser weldable resin composition can be produced by not mixing the components in advance, or by mixing only some of the components in advance, feeding the mixture to an extruder using a feeder, and melt-kneading the mixture. In addition, for example, a resin composition obtained by pre-mixing some of the components and feeding them to an extruder to melt-knead them can be used as a master batch, and this master batch can be mixed again with the remaining components and melt-kneaded to produce a laser welding resin composition. In addition, the master batch can be mixed with resin pellets as a base material and directly charged into a molding machine to produce a molded body. In addition, for example, when mixing a component that is difficult to disperse, the component that is difficult to disperse can be dissolved or dispersed in a solvent such as water or an organic solvent in advance, and then kneaded with the solution or dispersion to improve dispersibility.
[0098] [Molded body] The resin composition for laser welding of the present invention is molded into a laser-light-transmitting member for welding by irradiating a laser beam from the laser-light-transmitting member side to the laser-light-absorbing member side. The molding method can be any molding method generally used for thermoplastic resin compositions. Examples of the molding method include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc. Also, a molding method using a hot runner system can be used. Among these, injection molding methods such as injection molding, ultra-high speed injection molding, and injection compression molding, sheet extrusion molding, and profile extrusion molding are preferred.
[0099] The haze of the laser light transmitting member molded using the resin composition for laser welding of the present invention is preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and particularly preferably 1% or less, as measured at a thickness of 1 mm using a turbidimeter based on JIS K7136 and JIS K7361. Specific details of the method for measuring the haze are as described in the Examples.
[0100] [Laser light absorbing component] The laser-ray-transmitting member obtained from the laser-weldable resin composition of the present invention is laser-welded to another resin member (laser-ray-absorbing member) which is a counterpart member. The laser light absorbing side component of the counterpart material is preferably one obtained from a composition of thermoplastic resin (B). The thermoplastic resin (B) is preferably the same type as the transparent thermoplastic resin (A) described above, and examples of the thermoplastic resin include polycarbonate resin; acrylic resin such as polymethyl methacrylate resin; polyester resin such as polyethylene terephthalate (PET) resin; polystyrene resin; cyclic polyolefin resin; vinyl chloride resin, and the like, or a polymer alloy consisting of two or more of these thermoplastic resins. It is preferable to use polycarbonate resin or acrylic resin, and polycarbonate resin is particularly preferable.
[0101] In particular, since it is preferable from the viewpoint of weldability that both components have good compatibility, the composition of the thermoplastic resin (B) is preferably a resin composition of the same type as the above-mentioned laser welding resin composition for the laser light transmitting side component.
[0102] The above-mentioned thermoplastic resin (B) may be blended with the above-mentioned metal boride (B1) or tungsten oxide (B2), carbon black, near-infrared light absorbing dye, phosphite antioxidant, alkyl acid phosphate (metal salt), organic phosphonic acid, release agent, ultraviolet absorber, etc., as well as various other resin additives and other resins. The blending amount of each is within the same range as when the amount described for 100 parts by mass of the transparent thermoplastic resin (A) is replaced with 100 parts by mass of the thermoplastic resin (B).
[0103] The haze of the laser-light-absorbing member of the present invention is preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and particularly preferably 1% or less, as measured at a thickness of 1 mm using a turbidimeter based on JIS K7136 and JIS K7361. Specific details of the method for measuring the haze are as described in the Examples.
[0104] [Laser welding] The shapes of the laser-light-transmitting side member and the laser-light-absorbing side member are not limited, and may be a flat plate or a non-planar shape such as a curved surface, for example, a dome shape, a hemisphere shape, a cylinder shape, a box shape, a lid shape, a pyramid shape, a corrugated plate shape, or a complex shape combining planar and non-planar faces. In addition, the shape of the laser-light-transmitting side member and the shape of the laser-light-absorbing side member may be the same or different. The method of laser welding is not particularly limited and can be a normal method. For example, a laser weldable member obtained from the resin composition for laser welding of the present invention is used as a laser beam transmitting member, and is brought into face-to-face or butt-contact with a laser beam absorbing member as a counter member, and laser beam is irradiated from the transmitting member to weld and integrate the two members to form a laser welded body.
[0105] The type of laser light irradiated in laser welding may be any near-infrared laser light, and preferred examples include a YAG (yttrium aluminum garnet crystal) laser (wavelength 1064 nm) and an LD (laser diode) laser (wavelengths 808 nm, 840 nm, 940 nm).
[0106] The welded body integrated by laser welding may have any shape, size, thickness, etc., and is suitable as a component for products that require a high degree of transparency, such as parts for wearable devices, medical device parts, optical components, lighting equipment, lenses, lens covers, various displays, electric and electronic devices, laptops, pachinko, pachislot, amusement equipment such as games, office automation equipment, information terminal equipment, home appliances, vehicle parts (lights, interior components, panels), transparent partitions, panel components such as product displays, partition boards for vending machines, ticket machines, etc., signs, watches, accessories, etc. EXAMPLES
[0107] The present invention will be described in more detail below with reference to examples, but the present invention should not be construed as being limited to the following examples. The components used in the examples and comparative examples are as shown in Table 1 below.
[0108] [Table 1]
[0109] (Examples 1 to 16, Comparative Examples 1 to 3) [Production of resin pellets for laser light transmitting members] Among the components listed in Table 1 above, the components listed in Table 2 below were blended in the ratios (parts by mass) listed in Table 2, mixed in a tumbler mixer for 20 minutes, and then fed to an extruder (TEM26SX) manufactured by Shibaura Machine Co., Ltd., kneaded under conditions of a screw rotation speed of 200 rpm, a discharge rate of 20 kg / hr, and a cylinder temperature of 280° C., and extruded in a strand shape from the tip of the extrusion nozzle. The extrudate was quenched in a water tank and cut and pelletized using a pelletizer to obtain resin pellets a to h and x for the laser light transmission side member.
[0110] [Transmittance at 1070 nm (1 mmt, unit: %)] The pellets obtained above were dried at 120°C for 5 hours, and then an injection molding machine (JSW J55) was used to produce a 90mm x 60mm three-tiered plate (1mmt, 2mmt, 3mmt) at a cylinder temperature of 280°C and a mold temperature of 80°C. Using an ultraviolet-visible-near infrared spectrophotometer (Shimadzu Corporation, "UV-3600"), the transmittance (unit: %) at a wavelength of 1070 nm was determined in a 1 mm thick section of the three-tiered plate in accordance with ISO13468-2.
[0111] [Total light transmittance (1mmt, unit:%)] The total light transmittance (unit: %) of the 1 mm thick portion of the three-tiered plate obtained by the above method was measured in transmission mode D65 and at a 10° field of view using a spectroscopic haze meter SH 7000 manufactured by Nippon Denshoku Industries Co., Ltd., in accordance with JIS K7136 and JIS K7361. [Haze (1mmt, unit:%)] The haze of the 1 mm thick portion of the three-step plate obtained by the above method was measured in transmission mode D65 and at a 10° field of view using a spectroscopic haze meter SH 7000 manufactured by Nippon Denshoku Industries Co., Ltd., in accordance with JIS K7136 and JIS K7361.
[0112] [Haze after wet heat test (85℃, 85%RH, 1000h, 1mmt, unit:%)] The three-step plate obtained by the above method was held at 85° C. and 85% RH for 1000 hours, and then the haze (unit: %) of a 1 mm thick portion was measured in the same manner as above.
[0113] [Manufacturing resin pellets for laser light absorbing components] The polycarbonate resins A1 and A2 shown in Table 1 were used as the thermoplastic resin (B) used in the resin composition for the laser-light-absorbing member, and the components shown in Table 3 were blended in the ratios (parts by mass) shown in Table 3 among the components shown in Table 1, mixed for 20 minutes in a tumbler mixer, fed to an extruder (TEM26SX) manufactured by Shibaura Machine Co., Ltd., kneaded under conditions of a screw rotation speed of 200 rpm, a discharge rate of 20 kg / hr, and a cylinder temperature of 280° C., and extruded in a strand shape from the tip of the extrusion nozzle. The extrudate was quenched in a water tank, cut and pelletized using a pelletizer, and resin pellets A to H for the laser-light-absorbing member were obtained.
[0114] [Transmittance at 1070 nm (1 mmt), total light transmittance (1 mmt), haze (1 mmt), haze after wet heat test (85°C, 85% RH, 1000h, 1 mmt)] The pellets obtained above were dried at 120°C for 5 hours, and then an injection molding machine (JSW J55) was used to manufacture a 90 mm x 60 mm three-tiered plate (1 mmt, 2 mmt, 3 mmt) at a cylinder temperature of 280°C and a mold temperature of 80°C. The transmittance (1 mmt) at 1070 nm, haze (1 mmt), and haze after a wet heat test (85°C, 85% RH, 1000h, 1 mmt) were measured in the same manner as above.
[0115] [Evaluation of laser weldability] For the evaluation of laser welding, the pellets for the laser light absorbing component obtained above were dried at 120°C for 5 hours as the laser light absorbing component, and then an injection molding machine ("SE50" manufactured by Shibaura Machine Co., Ltd.) was used to mold an open-topped box-shaped container with a square bottom (outer bottom: 19.2 mm x 19.2 mm, inner bottom: 17.6 mm x 17.6 mm, side height: 10 mm, a rib with a rib width of 0.8 mm was provided on the outer side of the top of the box. The bottom side was opened for a removal test) under conditions of a cylinder temperature of 280°C and a mold temperature of 80°C.
[0116] As the laser light transmitting side component, the pellets for the laser light transmitting side component obtained above were dried at 120°C for 5 hours, and then an injection molding machine (Shibaura Machine Co., Ltd., "SE50") was used to mold a square flat lid material (20 mm long x 20 mm wide, 1 mm thick) under conditions of a cylinder temperature of 280°C and a mold temperature of 80°C. This was placed on top of the box to cover it, and the two were overlapped. The center of the rib of the overlapping part (total length of one revolution is 74 mm) was laser welded by irradiating it with laser light at a welding width of 1.2 mm and a rib width of 0.8 mm for the number of irradiation revolutions shown in Table 4. Laser welding was performed using a Panasonic "Galvano scanning type laser processing machine VL-W1" under the following conditions: laser wavelength 1070 nm, laser power and scan speed shown in Table 4, irradiation time approximately 1.1 to 1.5 seconds, pressure 0.3 MPa, and weld size 19.2 mm x 19.2 mm. The temperature of the welded portion during laser welding was measured with a thermography camera.
[0117] The appearance of the welded body was evaluated according to the following criteria. ◎: No bubbles or burnt areas 〇: Slight bubbles or burnt spots △: Bubbles and burnt spots are observed ×: Many bubbles and burnt areas
[0118] Using a standard type motorized test stand MX2-1000N and a standard type digital force gauge ZTS-1000N manufactured by Imada Co., Ltd., a removal test was performed by pushing the center of the container toward the transparent material side at 50 mm / min, and the bonding strength (unit: MPa) of the welded part was measured.
[0119] The results are shown in Table 2 below.
[0120] [Table 2]
[0121] [Table 3]
[0122] [Table 4] [Industrial Applicability]
[0123] The weldable member made of the laser weldable resin composition of the present invention has excellent transparency and laser weldability, and the laser welded member has excellent bonding strength, so that it can be suitably used as parts for various applications.
Claims
1. A laser welding resin composition for a laser light transmitting member, comprising, per 100 parts by mass of a transparent thermoplastic resin (A), 0.000001 to 0.05 parts by mass of at least one metal boride (B1) selected from the group consisting of La, Ce, Pr, Nd, Tb, Dy, Ho, Y, Sm, Eu, Er, Tm, Yb, Lu, Sr, and Ca, or 0.000001 to 0.05 parts by mass of at least one tungsten-based oxide (B2) selected from potassium tungsten oxide, rubidium tungsten oxide, cesium tungsten oxide, and thallium tungsten oxide.
2. 2. The laser welding resin composition according to claim 1, wherein the transparent thermoplastic resin (A) contains 10 to 100% by mass of a polycarbonate resin in the transparent thermoplastic resin (A).
3. The laser welding resin composition according to claim 1, further comprising 0.000001 to 0.05 parts by mass of carbon black per 100 parts by mass of the transparent thermoplastic resin (A).
4. The laser welding resin composition according to claim 1, further comprising a near-infrared absorbing dye in an amount of 0.000001 to 0.5 parts by mass per 100 parts by mass of the transparent thermoplastic resin (A).
5. The laser welding resin composition according to claim 1, further comprising a phosphite-based antioxidant in an amount of 0.005 to 0.5 parts by mass per 100 parts by mass of the transparent thermoplastic resin (A).
6. The laser welding resin composition according to claim 1, wherein the polycarbonate resin contains 10 to 80 mass % of an aromatic polycarbonate resin having a terminal structure containing an ester group.
7. A laser beam transmitting member comprising the laser welding resin composition according to any one of claims 1 to 6.
8. 8. The laser light transmitting lateral member according to claim 7, which has a haze of 20% or less at a thickness of 1 mm.
9. 8. A laser welded body obtained by laser welding the laser-transmitting member according to claim 7 to a laser-absorbing member.
10. 10. The laser welded body according to claim 9, wherein the laser-light-absorbing member contains 0.000001 to 0.05 parts by mass of carbon black per 100 parts by mass of the thermoplastic resin (B).
11. 10. The laser welded product according to claim 9, wherein the laser-absorbent side member contains 0.000001 to 0.5 parts by mass of the near-infrared absorbing dye per 100 parts by mass of the thermoplastic resin (B).
12. 10. The laser welded body according to claim 9, wherein the laser-light-absorbing side member contains 0.005 to 0.5 parts by mass of a phosphite antioxidant per 100 parts by mass of the thermoplastic resin (B).
13. 10. The laser welded article according to claim 9, wherein the laser-absorbent member has a haze of 20% or less at a thickness of 1 mm.
14. 10. The laser welded body according to claim 9, wherein a width of the laser welded portion between the laser-light-transmitting member and the laser-light-absorbing member is 0.5 to 10 mm.
Citation Information
Patent Citations
Laser welding method for lighting fixture for vehicle
JP2002292741A
Cited By
Laser-welded body and method for improving the aesthetic appearance of a laser-welded body
JP2026150103A
Laser-transmitting member and laser-welded body
JP2026150104A